Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Mon corps a-t-il un sexe? Détermination du sexe et contraintes du genre. - Guillot, Vincent (Identités intersexes: identités en débat, 2013)
L'Observatoire des transidentités (O.D.T.) est une interface de visibilité des questions trans, militantes comme universitaires. Dans cet ouvrage, les responsables de l'O.D.T. ont restitué des débats, des textes et des rencontres autour des questions transidentitaires (classifications médicales, dépsychiatrisation, mouvements LGBTIQ, films et reportages, Trans and Queer studies, etc.).. Les contributeurs de ce livre, qu'ils soient chercheurs ou militants, proposent des éléments de représentations dépathologisants autour des transidentités et une réflexion transdisciplinaire sur les multiples formes que prennent aujourd'hui les identités de genre. Ce second volume porte son attention sur la question intersexe et sur le(s) communautés LGBT.
Section: 168 p. : illustrations ; 24 cm.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Fear of a queer planet queer politics and social theory - Warner, Michael; Social Text Collective (University of Minnesota Press, 2007)
In recent years, lesbians and gay men have developed a new, aggressive style of politics. At the same time, innovative intellectual energies have made queer theory an explosive field of study. In "Fear of a Queer Planet", Michael Warner draws on emerging new queer politics, and shows how queer activists have come to challenge basic assumptions about the social and political world. Existing traditions of theory - Marxism, cultural studies, psychoanalysis, anthropology, legal theory, nationalism, and antinationalism - have too often presupposed a heterosexual society, as the essays in this volume demonstrate. "Fear of a Queer Planet" suggests a new agenda for social theory. It moves beyond the idea that lesbians and gay men share a minority identity and special interests and that their issues can be subordinated to more general social conflicts. Instead, Warner and the other contributors to this volume show that queer sexualities take many forms, are the subject of many kinds of conflict and struggles, and must be taken as a starting point in thinking about cultural politics. This collection explores the impact of ACT UP, Queer Nation, multiculturalism, the new religious right, outing, queerness, postmodernism, and other shifts in the politics of sexuality. The authors featured speak from different backgrounds of gender, race, nationality, and discipline. Together, they show how struggles over sexuality have profound implications for progressive politics, social theory, and cultural studies. Michael Warner has written extensively on censorship and the public sphere, the construction of American literary history, and the social and political implication of literary theories. He is author of "The Letter of the Republic: Publication and the Public Sphere in Eighteenth-Century America" and co-editor of "The Origins of Literary Studies in America: A Documentary Anthology".
Section: 1 v. (XXXI-334 p.) : illustrations ; 22 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; histoire et politique; militance; premier cycle; périodes historiques; queer; science politique et droit; sciences politiques; soc2014; thématiques; théories sociales

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Publisher: Taylor & Francis
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Corvallis Lesbian Avengers collection, 1990-2000. - Corvallis Lesbian Avengers. (1990)
La collection Corvallis Lesbian Avengers documente les activités du chapitre Corvallis des Lesbian Avengers tout au long des années 1990. Les Corvallis Lesbian Avengers étaient une section locale de l'organisation nationale Lesbian Avengers. Créés à l'origine en 1992 à New York, les Lesbian Avengers étaient un groupe d'action directe axé sur des questions vitales pour la survie et la visibilité des lesbiennes. La majeure partie de la collection est constituée d'albums photo et d'albums contenant des photographies, des coupures de presse, des dépliants, des œuvres d'art, de la poésie et d'autres documents papier. La collection comprend également une petite collection d'artefacts, un calendrier annoté et 3 numéros du zine Necessary Friction produit par les Corvallis Lesbian Avengers. L'ensemble de la collection est numérique et entièrement disponible sur demande du client ou pour une utilisation dans la salle de lecture du SCARC. Des entretiens d'histoire orale de plusieurs membres fondateurs des Corvallis Lesbian Avengers contenant des informations supplémentaires peuvent être trouvés dans la collection d'histoire orale des archives Queer de l'OSU (OH 034) . Ceux-ci incluent des entretiens avec DJ Travers , Julie Derrick et Brian Parks .
https://archiveswest.orbiscascade.org/ark:/80444/xv178746
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; lesbianisme; militance; personnes lesbiennes; périodes historiques; queer; régions géographiques; thématiques; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis